1994
DOI: 10.1088/0022-3727/27/8/006
|View full text |Cite
|
Sign up to set email alerts
|

The laser welding of thin metal sheets: an integrated keyhole and weld pool model with supporting experiments

Abstract: An integrated mathematical model for laser welding of thin metal sheets under a variety of laser material processing conditions has been developed and tested against the results of experiments. Full account is taken in the model of the interaction of the laser-generated keyhole with the weld pool. Results calculated from the model are found to agree well with experiment for appropriate values of the keyhole radius. The analysis yields values for power absorption in the metal. In a complementary calculation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 5 publications
0
35
0
1
Order By: Relevance
“…b [11,31,33,[38][39][40][41]; c [11,[33][34][35][36][37][42][43][44]; d [11,12,31,33,38,41,42,45]; e [30]; f [32,42]; g [42,45]; h [7,8]; i [8]; j [43,46]; k [38,41,47]; l [44,46].…”
Section: Melt-pool Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…b [11,31,33,[38][39][40][41]; c [11,[33][34][35][36][37][42][43][44]; d [11,12,31,33,38,41,42,45]; e [30]; f [32,42]; g [42,45]; h [7,8]; i [8]; j [43,46]; k [38,41,47]; l [44,46].…”
Section: Melt-pool Geometrymentioning
confidence: 99%
“…Ducharme et al [42] presented an integrated model of laser welding, taking into account the conditions in the keyhole as well as in the meltpool, interactively. ese authors investigated the influence of process parameters on the melt-pool shape.…”
Section: Appendixmentioning
confidence: 99%
“…For a CO 2 laser and steel workpiece, its widely used value is 0.08. However, it is also modifiable because (a) the keyhole wall is boiling and this could affect the Fresnel absorption and (b) the method used to calculate the Fresnel absorption is approximated, and the use of a large value of e could compensate for the approximations made [17]. This paper suggested the value of e to be 0.2 and showed that the results are acceptable for mild steel and CO 2 laser, compared with experiments.…”
Section: Heat Source Modelsmentioning
confidence: 99%
“…The areas of the prediction and optimization of the composition and properties of materials obtained in different technological processes are especially promising [5][6][7][8]21,[24][25][26][27][28][29][30][31][32][33]. Some of the results were obtained from the modeling of the process of the formation of a weld pool [5,30], from the modeling of metal transfer [28,31,32] and weld metal transformations [22,23,27,30], and from the modeling of temperature distribution [25] and electrode melting [24], from metallurgical modeling of the welding [11,26] and diffusion-controlled kinetics of metallurgical processes [6,20,2].…”
Section: Computer Modeling As An Up-to-date Approach To New Welding Mmentioning
confidence: 99%
“…Some of the results were obtained from the modeling of the process of the formation of a weld pool [5,30], from the modeling of metal transfer [28,31,32] and weld metal transformations [22,23,27,30], and from the modeling of temperature distribution [25] and electrode melting [24], from metallurgical modeling of the welding [11,26] and diffusion-controlled kinetics of metallurgical processes [6,20,2].…”
Section: Computer Modeling As An Up-to-date Approach To New Welding Mmentioning
confidence: 99%